(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This research deals with a comprehensive view of the reality of practicing public relations in government agencies in the Eastern Province, by addressing the concepts of public relations and its role in shaping the image of the agency, as a human communication activity, and in light of the radical transformations witnessed by the world and the field of communication due to rapid technological developments and changing public behavior, with the emergence of social media and the increase in public interaction, public relations have become more interactive and transparent. Also, the increasing competition between institutions imposes on public relations practitioners to devise new and innovative strategies to reach the target audience. In light of the fact that public relations is a fundamental pillar in the work of any system, this research deals with part of the reality of public relations in government organizations in the Eastern Province, considering the public relations function an important pillar in building perceptions and relationships with the public. In the Kingdom of Saudi Arabia, after the launch of the Kingdom’s Vision 2030, communication activities have re-emerged in the government work arena, and witnessed a transformation in work methods and mechanisms. These activities focused on reflecting the true image of the achievements of the entities working in the field, and for these activities to stem from a deep understanding of the public and its aspirations, with a focus on new media, as they are the closest to the target group.